Školjkarica Haematopus ostralegus - Bordjan, Dejan (Acrocephalus, 2018)
38 individuals seen migrating over stony meadows NW of Povljana in SE part of Pag Island on 29 Apr 2018; probably one of the largest flocks recorded in Croatia
Keywords: Haematopus ostralegus; ornitologija; ptice; školjkarica